Walking Exercise Therapy in Reducing Random Blood Glucose Levels Among Patients with Type 2 Diabetes Mellitus - Amalia, Riska; Syah, Afni Yan; Juliana, Juliana (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Walking exercise is one of the simplest and most cost-effective therapeutic approaches that can improve insulin sensitivity and promote glucose utilization for patients with Type 2 Diabetes Mellitus (T2DM).  This study aimed to determine the effectiveness of walking exercise therapy in lowering random blood glucose levels among patients with T2DM. A quasi-experimental design with a one-group pretest–posttest approach was used. The study involved 21 respondents with T2DM who were members of the Posbindu PTM in Gampong Lam Ujong Meunasah Manyang, Aceh Besar. The intervention consisted of walking exercise sessions lasting 30–45 minutes, performed three times per week for four consecutive weeks. Random blood glucose (RBG) levels were measured before and after the intervention using an Accu-Chek glucose meter. Data were analyzed using the Wilcoxon signed-rank test with a significance level of ? 0.05. The results showed a significant decrease in RBG levels from a mean of 351.19 mg/dL before the intervention to 254.71 mg/dL after the four-week exercise program (p = 0.000). These findings indicate that walking exercise therapy effectively reduces random blood glucose levels in patients with Type 2 Diabetes Mellitus. Therefore, nurses and community health practitioners are encouraged to incorporate walking exercise therapy into diabetes care and education programs as part of lifestyle modification strategies to achieve better glycemic control.